2022
DOI: 10.1038/s41398-022-02108-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential microRNA expression analyses across two brain regions in Alzheimer’s disease

Abstract: Dysregulation of microRNAs (miRNAs) is involved in the pathogenesis of neurodegenerative diseases, including Alzheimer’s disease (AD). Hitherto, sample sizes from differential miRNA expression studies in AD are exceedingly small aggravating any biological inference. To overcome this limitation, we investigated six candidate miRNAs in a large collection of brain samples. Brain tissue was derived from superior temporal gyrus (STG) and entorhinal cortex (EC) from 99 AD patients and 91 controls. MiRNA expression w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 45 publications
3
16
0
1
Order By: Relevance
“…19 These seemingly conflicting results could possibly be attributed to differences in miR expression that are specific to disease stages and tissue types, as has been documented in neurodegenerative disorders. 35 Our work thus reinforces the usefulness of certain miRNAs from our previous miRNA-seq experiments and illustrates their applicability in a more easily accessible specimen, available from routine clinical diagnostics. In accord with miRNAs being suitable LBD biomarkers, a recent study reported a consistent deregulation of 12 miRNAs across the RBD continuum, including DaT-negative iRBD, DaT-positive iRBD, and LBD phenoconverted iRBD, both in cross-sectional and longitudinal analyses.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…19 These seemingly conflicting results could possibly be attributed to differences in miR expression that are specific to disease stages and tissue types, as has been documented in neurodegenerative disorders. 35 Our work thus reinforces the usefulness of certain miRNAs from our previous miRNA-seq experiments and illustrates their applicability in a more easily accessible specimen, available from routine clinical diagnostics. In accord with miRNAs being suitable LBD biomarkers, a recent study reported a consistent deregulation of 12 miRNAs across the RBD continuum, including DaT-negative iRBD, DaT-positive iRBD, and LBD phenoconverted iRBD, both in cross-sectional and longitudinal analyses.…”
Section: Discussionsupporting
confidence: 79%
“…This result differs from previous findings indicating that miR‐486p is upregulated in gut biopsies of PD cases 19 . These seemingly conflicting results could possibly be attributed to differences in miR expression that are specific to disease stages and tissue types, as has been documented in neurodegenerative disorders 35 . Our work thus reinforces the usefulness of certain miRNAs from our previous miRNA‐seq experiments and illustrates their applicability in a more easily accessible specimen, available from routine clinical diagnostics.…”
Section: Discussionsupporting
confidence: 47%
“…Postmortem brain tissues from four patients with AD and five age-matched controls diagnosed by neurology were provided by the Tissue Bank of the Institute of Geriatrics, Chinese PLA General Hospital, and Chinese PLA Medical Academy, and a detailed description of the patient information is provided in previous studies ( 58 , 84 ). Total RNA-seq data from entorhinal cortex samples from 90 patients with AD and 84 healthy donors were provided by the Oxford Brain Bank ( 85 ), and the use of these human tissue samples for this study was approved by the Ethics Committees of the University of Lübeck. This study was approved by the Ethics Committee of Tongji Medical College, Huazhong University of Science and Technology.…”
Section: Methodsmentioning
confidence: 99%
“…MREs in Mov10 for all four tested miRNAs miR‐138‐5p, miR‐30‐5p, miR‐16‐5p, and miR‐153‐3p in mESCs are conserved in the 3'UTR sequence of hMOV10, raising the possibility that this mechanism regulating MOV10 expression may also be conserved in humans. Of note, miR‐138‐5p and miR‐153‐3p are highly expressed in the human brain (Ludwig et al , 2016), and both miRNAs are downregulated in brain pathologies from Alzheimer's disease patients (Long et al , 2012; preprint: Dobricic et al , 2021). The activation of expression and mobility of transposable elements has been reported in a majority of neurological disorders (Terry & Devine, 2020) and certain cancers (Xiao‐Jie et al , 2016).…”
Section: Discussionmentioning
confidence: 99%